Effects Of Carbaryl Exposure On The Protein Content Of Cyprinus Carpio (Cuestiones de Fisioterapia, 2025)
The effect of carbaryl on the protein content of gill, muscle and liver tissues of C. carpio was studied. The fishCyprinus carpio was employed as an indicator animal and its gill, muscle, liver tissue was analyzed forpesticide residue accumulation where in the biochemical changes such as protein was found to be depleteddue to toxicity of pesticides. Subsequently an increase protein content was noted in the biodegradationexperimental sets.